2022
DOI: 10.1088/1361-6560/ac6aa1
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance of adaptive axial FOV PET scanners with a sparse detector block rings or a checkerboard configuration

Abstract: Objective: Using Monte-Carlo simulations, we evaluated the physical performance of a hypothetical state-of-the-art clinical PET scanner with adaptive axial field-of-view (AFOV) based on the validated GATE model of the Siemens Biograph VisionTM PET/CT scanner. Approach: Vision consists of 16 compact PET rings, each consisting of 152 mini-blocks of 5 × 5 Lutetium Oxyorthosilicate crystals (3.2 × 3.2 × 20 mm3). The Vision 25.6 cm AFOV was extended by adopting (i) a sparse mini-block ring (SBR) configuration of 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…It is also possible to efficiently obtain a large amount of PET data encompassing the entire thorax in a single breath-hold. This approach effectively mitigates motion artefacts caused by breathing and improves PET-CT registration and PET quantification accuracy [181]. In addition, this reduction in acquisition time makes it more comfortable for patients suffering pain during the examination with minimal motion artefacts.…”
Section: Effect Of Afov On Pet Performancementioning
confidence: 99%
“…It is also possible to efficiently obtain a large amount of PET data encompassing the entire thorax in a single breath-hold. This approach effectively mitigates motion artefacts caused by breathing and improves PET-CT registration and PET quantification accuracy [181]. In addition, this reduction in acquisition time makes it more comfortable for patients suffering pain during the examination with minimal motion artefacts.…”
Section: Effect Of Afov On Pet Performancementioning
confidence: 99%
“…2. A sparse long axial FOV PET design of about 1-1.4 m, but with ~ 50% reduced manufacturing cost, by eliminating ~ 50% of the detector elements or blocks This design concept delivers large system sensitivity gains in body imaging, about 4 × less than a fully populated 1-m axial FOV TB-PET system, but still 4 × higher than a standard 25-cm axial FOV scanner [13][14][15][16][17]. Regarding peak axial slice sensitivity, a gain reduced by 2 times relative to a full 100 cm but still 2 times higher than a full 25-cm axial FOV PET system is expected.…”
Section: A Medium-cost Total-body Pet Scannermentioning
confidence: 99%
“…Furthermore, thanks to the above sensitivity performance specifications, the sparse configuration attains the smallest axial variance in axial slice sensitivity between the centers and the edges of the axial FOV, thus resulting in the smallest axial noise variance in the reconstructed images, compared to a full 100-cm-long TB-PET system. Studies have shown that the introduction of a relatively large number of small axial gaps uniformly distributed between the existing detector elements or blocks can result in artifact-less reconstructed images of nearly doubling the axial FOV, similar NEMA contrast recovery and only a slightly elevated background image noise [13][14][15][16][17]. These results are a consequence of sparse detector designs taking advantage of the redundancy of data used in the 3D reconstruction.…”
Section: A Medium-cost Total-body Pet Scannermentioning
confidence: 99%
“…All the mentioned facts motivate the investigation to find a cost-effective solution to reduce the final construction cost of TB PET [7]. One of the recently suggested solutions is the sparse detector configuration [18,19]. In the proposed sparse geometry, there are intervals between detectors leading to large AFOV with less number of scintillation crystals and electronics.…”
Section: Introductionmentioning
confidence: 99%